Distribution of pathogenicity islands among Colombian isolates of Salmonella - Miryan Margot Sánchez-Jiménez; Nora María Cardona-Castro; Nunzia Canu; Sergio Uzzau; Salvatore Rubino (Journal of Infection in Developing Countries)
Introduction: Salmonella pathogenicity islands (SPIs) are regions scattered along the bacterial chromosome, with an acknowledged pivotal role during gastrointestinal and systemic infection. The distribution of SPIs has been investigated in reference strains. However, there is a lack of studies on their presence and/or assortment within the genomes of Salmonella enterica (S. enterica) serovars that circulate in different geographical regions. Therefore, in this study, we aimed to determine the presence of genes of the pathogenicity islands 1 to 5 (SPI-1 to 5), in Salmonella clinical isolates from Colombian patients with systemic and enteric outcomes.